1997
DOI: 10.1002/(sici)1097-0215(19970304)70:5<619::aid-ijc21>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ALL-trans-retinoic acid and 13-cis-retinoic acid on breast-cancer cell lines: Growth inhibition and apoptosis induction

Abstract: Interest has been increasingly focused on all-trans-retinoic acid (tRA) and 13-cis-retinoic acid (13cRA) in cancer chemoprevention and treatment. We have examined the in vitro effects of these 2 retinoic acids (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 15 publications
3
65
0
Order By: Relevance
“…ATRA was found to decrease cell growth of MCF-7 cells (Toma et al, 1997). This was confirmed in the present paper by cytometric data, after DNA content evaluation and BrdU vs DNA dual-parameter measurements.…”
Section: Discussionsupporting
confidence: 89%
“…ATRA was found to decrease cell growth of MCF-7 cells (Toma et al, 1997). This was confirmed in the present paper by cytometric data, after DNA content evaluation and BrdU vs DNA dual-parameter measurements.…”
Section: Discussionsupporting
confidence: 89%
“…Except where otherwise stated, all cells were assessed following 6 days of ATRA/RAMBAs treatments. We point out that several researchers Toma et al, 1997) including us (Patel et al, 2004) have found that induction of several biochemical pathways in most cancer cell line become evident only after 6 days of ATRA/retinoid treatment.…”
Section: Effects Of Rambas On Mcf-7 T-47d and Mda-mb-231 Cell Growthmentioning
confidence: 75%
“…Because ATRA and most retinoids control cell proliferation via apoptosis among several other mechanisms in a variety of cancers Toma et al, 1997;Kotake-Nara et al, 2002;Afonja et al, 2004;Simeone and Tari, 2004) and also because of the cell cycle analysis data that suggests accumulation of cell in the sub-G phase, the apoptotic potential of our RAMBAs was evaluated. Retinoic acid metabolism blocking agents-induced apoptosis in MCF-7 and T47D cells was examined in three independent experiments with ATRA and 4-HPR as positive controls.…”
Section: Apoptosis Induced By Rambasmentioning
confidence: 99%
“…The main mechanism by which ATRA inhibits the proliferation of breast cancer cells is by inducing G1 cell cycle arrest (Wilcken et al, 1996;Toma et al, 1997Toma et al, , 1998Mangiarotti et al, 1998). Breast cancer cells became growth arrested when they were incubated with ATRA for 3 or more days.…”
Section: Discussionmentioning
confidence: 99%